Influence of abiotic factors on the co-occurrence of rugose spiralling whitefly, Aleurodicus rugioperculatus Martin and Bondar's Nesting Whitefly, Paraleyrodes bondari Peracchi in coconut palms - Gopianand, L.; Kathirvelu, C. (Journal of Plantation Crops, 2023)
-